2017
DOI: 10.1038/leu.2017.273
|View full text |Cite
|
Sign up to set email alerts
|

Activation of RHOA–VAV1 signaling in angioimmunoblastic T-cell lymphoma

Abstract: Somatic G17V RHOA mutations were found in 50–70% of angioimmunoblastic T-cell lymphoma (AITL). The mutant RHOA lacks GTP binding capacity, suggesting defects in the classical RHOA signaling. Here, we discovered the novel function of the G17V RHOA: VAV1 was identified as a G17V RHOA-specific binding partner via high-throughput screening. We found that binding of G17V RHOA to VAV1 augmented its adaptor function through phosphorylation of 174Tyr, resulting in acceleration of T-cell receptor (TCR) signaling. Enric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
106
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(123 citation statements)
references
References 50 publications
1
106
0
Order By: Relevance
“…Among the 7 patients with PTCL‐NOS histology, 2 patients achieved a durable CR, 2 patients had objective response and 1 patient had SD. Recently; it was shown that dasatinib efficiently inhibits aberrant VAV1 activation and subsequent signalling by RHOA G17V and VAV1 mutations in angioimmunoblastic T‐cell lymphoma (AITL) (Fujisawa et al , ). Consistent with this observation, 1 AITL patient in our cohort achieved a short‐lived PR.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 7 patients with PTCL‐NOS histology, 2 patients achieved a durable CR, 2 patients had objective response and 1 patient had SD. Recently; it was shown that dasatinib efficiently inhibits aberrant VAV1 activation and subsequent signalling by RHOA G17V and VAV1 mutations in angioimmunoblastic T‐cell lymphoma (AITL) (Fujisawa et al , ). Consistent with this observation, 1 AITL patient in our cohort achieved a short‐lived PR.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, combination of these methods increased the detection rate of RHOA mutations at the p.Gly17 position. We recently reported essential downstream signaling of G17V RHOA mutations in PTCL: the G17V mutant RHOA hyper‐activated the T‐cell receptor (TCR) signaling pathway through specific binding to VAV1 protein, an essential component in TCR signaling . The other RHOA mutants at the p.Gly17 position presumably have a similar function, although it has not been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Seven per cent of PTCL showed rearrangements of Vav guanine nucleotide exchange factor 1 (VAV1), which is normally a regulator of RHOA activity as well as other pathways. Indeed, it has been shown that RHOA (p.Gly17Val) binding to VAV1 increases TCR signalling (Fujisawa et al , ).…”
Section: Genetic Aberrations In Aitl and Ptcl‐nosmentioning
confidence: 99%
“…The understanding that activation of TCR signalling is required for lymphomagenesis may also provide new therapeutic avenues. The tyrosine kinase inhibitor dasatinib has been shown to block VAV1 phosphorylation and increased TCR signalling due to RHOA (p.Gly17Val) in a T‐cell line (Fujisawa et al , ). ITK is expressed in AITL and we have demonstrated in cell lines (Mamand et al , ) and also in a mouse model of Tfh lymphoma (Allchin et al , ) that ibrutinib, a dual ITK and Bruton's tyrosine kinase (BTK) inhibitor, can repress growth and reduce tumour size.…”
Section: Routes To the Clinicmentioning
confidence: 99%